The Religious Sexual Education in Post-Revolutionary Iran: Redefining Tamkin and the Control of Sexuality - Nafiseh Sharifi (Gender a Výzkum, 2019)
This paper looks at the religious discourse of sexuality in post-revolutionary Iran. Based on my ethnographic fieldwork in Tehran, I discuss how in state-sponsored publications and official education traditional religious rules of sexuality such as tamkin are redefined in relation to society’s new demands. I discuss the role played by religious workshops for married couples in justifying Islamic moral codes of behaviour that regulate and control Iranians’ sexual lives.